Interactive Maps on Variant Phase Spaces– From Measurements - Micro Ensembles to Ensemble Matrices on Statistical Mechanics of Particle Models - Zheng, Jeffrey; Zheng, Christian; Kunii, Tosiyasu (IntechOpen, 2013)
None